Mežstilevaâ inteferenciâ kak dominanta stilistiko rečevogo povedeniâ v russkoj slovesnoj kul’ture êpohi Velikoj otvečstnnoj vojny - Protopopova, Ol’ga V.. (Stylistyka, 2019)
The article analyzes the stylistic features of speech during the Great Patriotic War (1941–1945): Reports of the Soviet Information (the SIS), directives governing the country and the army, appeared in the press only in the 1990s. The analysis showed a convergence of seemingly polar genres, stylistically marked in the application of means – the communication was carried out by means of the verbal culture of the day. Signs of between-style interference were found in the texts of administrative genres: at the lexical level – emotive words and expressions, at the level of grammar – structures of expressive syntax. But it is important that all the expressive means do not destroy the basic quality of business texts – the imperative, but rather strengthen it. All this is due to the need to implement the intentions of the impact on the senses, the morale of the Soviet people, to inspire the struggle and inform about prescribed actions.